1990
DOI: 10.1002/bjs.1800771006
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative air testing of colorectal anastomoses: A prospective, randomized trial

Abstract: A total of 145 consecutive patients receiving a colorectal anastomosis were randomized to 'test' or 'no test' once the anastomosis had been completed. Anastomotic testing was performed with the pelvis filled with saline and the rectum distended by sigmoidoscopic insufflation of air. Any leaks demonstrated were oversewn. A water-soluble contrast enema was performed on the tenth postoperative day. Seventy-four patients were randomized to 'test' and 71 to 'no test' but one patient was withdrawn from each group le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 6 publications
5
108
0
7
Order By: Relevance
“…1 We find that the use of this retractorc an damage thea rticulars urfaceo ft he humeralh ead and interferes with theoperative field. We describe an alternativemethod that avoids these complications.…”
Section: Introductionmentioning
confidence: 80%
“…1 We find that the use of this retractorc an damage thea rticulars urfaceo ft he humeralh ead and interferes with theoperative field. We describe an alternativemethod that avoids these complications.…”
Section: Introductionmentioning
confidence: 80%
“…One early study recommended a pressure of 25 cm saline (18.4 mmHg) as being sufficient to detect leaks while being within physiological limits [26]. Another study found that intrarectal pressure could not be raised above 35 mm Hg because of venting of air [27]. Insufflation is typically performed until the rectum is 'optimally' distended, which may be limited by air leak along the sigmoidoscope [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports recommended intraoperative repair of stapled anastomotic defects using interrupted sutures as a safe alternative to a diverting colostomy or ileostomy [7,10]. On the other hand, Ricciardi et al [11] suggested that suture repair alone in the setting of a positive air leak results in postoperative CAL because the postoperative clinical leak rate (12.2%) in their patients was significantly higher than the rate (3.8%) in anastomosis with initially negative intraoperative leak test results [11].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the air leak test (ALT) is reportedly the most frequently performed intraoperative test to identify a mechanically insufficient anastomosis [6]. A randomized prospective study of the intraoperative ALT showed significant reduction of postoperative leakage in the tested group [7]. Direct insufflation of air at the level of the anastomosis by intraoperative colonoscopy (IOCS) may be reliable for ensuring adequate intraluminal pressure to demonstrate a leak.…”
Section: Introductionmentioning
confidence: 99%